2018
DOI: 10.1007/s11250-018-1574-y
|View full text |Cite
|
Sign up to set email alerts
|

Increasing levels of supplementation for crossbred steers on pasture during the dry period of the year

Abstract: The aim of this study was to evaluate the effect of increasing concentrate supplementation levels on the intake, nutrient digestibility, and performance of crossbred steers during the dry period of the year. The experiment was developed on Princesa do Mateiro farm, in the municipality of Ribeirão do Largo, located in the southwest region of Bahia State, Brazil. Forty uncastrated male crossbred (½ Holstein-Zebu) steers with an average body weight (BW) of 232.55 ± 24.97 kg were distributed into four treatments i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…Depending upon economic conditions and farmers´ preferences (Poppi et al 2018), supplementation of cattle grazing these tropical pastures would be expected to increase their performance. Several studies conducted in the Brazilian Cerrado have unequivocally shown a positive response of fattening cattle grazing Brachiaria-based pastures to energy and protein supplements (da Silva-Marques et al 2018a, 2018bNeves et al 2018). On the other hand, supplementation of tropical beef cows has been little studied, but da Silva et al (2017) reported a small positive effect on weight losses in early lactation when Nellore (Bos indicus) cows, grazing Bd were supplemented with concentrates during the last 60 days of pregnancy; nevertheless, the effect of supplementation did not translate into reduced calving intervals.…”
Section: Discussionmentioning
confidence: 99%
“…Depending upon economic conditions and farmers´ preferences (Poppi et al 2018), supplementation of cattle grazing these tropical pastures would be expected to increase their performance. Several studies conducted in the Brazilian Cerrado have unequivocally shown a positive response of fattening cattle grazing Brachiaria-based pastures to energy and protein supplements (da Silva-Marques et al 2018a, 2018bNeves et al 2018). On the other hand, supplementation of tropical beef cows has been little studied, but da Silva et al (2017) reported a small positive effect on weight losses in early lactation when Nellore (Bos indicus) cows, grazing Bd were supplemented with concentrates during the last 60 days of pregnancy; nevertheless, the effect of supplementation did not translate into reduced calving intervals.…”
Section: Discussionmentioning
confidence: 99%
“…To date, animal performance has been compared in steers ( 10 ), beef cows ( 11 ), and calves ( 12 ) under grazing and supplementation conditions, mainly reflecting a mixed effect of feed type and amounts. However, few studies have compared the growth performance in heifers by supplementing concentrate until now.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, Neves and colleagues [22] investigated the effect of increasing concentrations of concentrated supplementation on intake, nutrient digestibility and performance of crossbred steers during the dry period of the year. Based on the findings, the authors recommended protein supplementation of 0.5% body weight (BW) with 24% CP to obtain gains of up to 0.500 kg/ day for steers in pasture systems during the post-weaning phase in the dry season of the year.…”
Section: Performance Of Beef Cattle Fed Tropical Pasture Supplementedmentioning
confidence: 99%